Self-regulation and self-efficacy as mediators of achievement goals and leisure time physical activity: a proposed model - G. Erturan; R. McBride; B. Agbuga (IP Iermakov S.S., 2020)
Background and Study Aim : The purpose of this study was to examine the mediating role of self-efficacy and self-regulation between achievement goals and leisure time physical activity among Turkish high school students. Material and Methods : Four hundred and sixty-four high school students (216 male; 248 female) enrolled in physical education classes voluntarily participated in the study. To assess whether the data fit the proposed model structural equation modelling was used. Results: Results revealed that self-efficacy mediated the effects of mastery-approach, mastery-avoidance, and performance-approach goals on leisure time physical activity. Self-regulation was not a mediator of achievement goals and did not predict leisure time physical activity. Conclusions: This study revealed the importance of self-efficacy in physical education to promote students' leisure time physical activity.